Study on an α-glucosidase inhibitor separated from Cyclocarya paliurus leaves - Shen Bing; Zhao Wei; Ou Wenbin; Zhou Shengmei; Liu Jun; Meng Fanguo (浙江大学学报. 农业与生命科学版, 2014)
Cyclocarya paliurus (Batal.) Iljinskaja is a multiple-function tree species in China. Due to its hypotensive and hypoglycemic functions, C. paliurus leaves have been used to make beverage over a long period of time. Studies of C. paliurus (Batal.) Iljinskaja began in 1970s in China. A variety of compounds, including flavonoids, terpenoids, alkaloids, saccharides, alcohol compounds, phenolic compounds and carboxylic acids, etc., have been separated and purified from C. paliurus leaves. Recently, hypoglycemic effects of crude extract from C. paliurus leaves in alloxan diabetic mouse have been reported. So far, only a few studies were performed to separate and analyze the active components from C. paliurus.The active components of C. paliurus leaves, which inhibit the activity of α-glucosidase, were separated and purified by using water extraction, alcohol precipitation, Sephadex LH-20 column chromatography and semi-preparative liquid chromatography. Finally, a white powder compound was obtained with yield of 0.03‰. The compound contained the characteristics of polysaccharide by analysis of its ultraviolet spectrum and high resolution mass spectrum, and showed a potent inhibitory effect against α-glucosidase activity with IC50 (the compound concentration of 50% inhibitory rate) of 3.13 μg/mL. The inhibition time of the compound against enzymatic activity was less than 0.5 min, indicating the high affinity between the inhibitor and the enzyme. The inhibition of enzymatic activity by the compound was hybrid non-competitive.In conclusion, the water extract of C. paliurus leaves and the separated powder compound with polysaccharide characteristics have potent inhibitory effects against α-glucosidase activity.